2014
DOI: 10.1016/j.bbagen.2014.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Methyl pyruvate rescues mitochondrial damage caused by SIGMAR1 mutation related to amyotrophic lateral sclerosis

Abstract: ATP supplementation by MP represents a potential therapeutic strategy to treat ALS caused by SIGMAR1 mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 67 publications
9
44
0
Order By: Relevance
“…One striking feature of the localization pattern of s-1R-E102Q was the presence of large, bright puncta, which colocalized poorly with the ER-resident protein BiP. Although little is known about the oligomerization dynamics of s-1R-E102Q, previous work has suggested that these puncta reflect cytosolic aggregates (Tagashira et al, 2014). Our data also suggest that these aggregates may reflect mutant s-1R clustering at ER subcompartments where BiP is excluded.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…One striking feature of the localization pattern of s-1R-E102Q was the presence of large, bright puncta, which colocalized poorly with the ER-resident protein BiP. Although little is known about the oligomerization dynamics of s-1R-E102Q, previous work has suggested that these puncta reflect cytosolic aggregates (Tagashira et al, 2014). Our data also suggest that these aggregates may reflect mutant s-1R clustering at ER subcompartments where BiP is excluded.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, subsequent work has demonstrated that the s-1R binds to binding immunoglobulin protein (BiP) when not activated by an agonist (Hayashi and Su, 2007a). However, the subcellular dynamics of the two s-1R mutants that underlie neuromuscular diseases, s-1R-E102Q (Tagashira et al, 2014) and s-1R-D31-50 (Li et al, 2015), are poorly characterized. We performed localization experiments using confocal imaging on primary MEF or CHO cells transiently transfected with the fluorescently tagged proteins s-1R-YFP and BiP-mCh to determine their intracellular localization.…”
Section: Resultsmentioning
confidence: 99%
“…Eventually, strategies to prevent ATP loss have been identified to exert an antioxidative stress effect [48]. Recently, MP accentuating ATP has also been regarded as a clinical approach to curing mitochondrial dysfunction due to mutated SIGMAR1, leading to amyotrophic lateral sclerosis [49].…”
Section: Discussionmentioning
confidence: 99%
“…For these genes, identified mutations comprised 20 % in SOD1 gene [6], 5 % in TARDBP and FUS genes [7], and more than 40 % in C9ORF72 [8]. In addition to these, mutations in alsin, senataxin (SETX), spatacsin, angiogenin (ANG), factor-induced gene 4 (FIG 4), optineurin (z), and sigma receptor 1 (SIGMAR1) have also been reported [9,10].…”
Section: Introductionmentioning
confidence: 91%